Cross-Border Investing with Tax Arbitrage: The Case of German Dividend Tax Credits - McDonald, Robert L. (Review of Financial Studies, 2001)
German dividends typically carry a tax credit which makes the dividend worth 42.86% more to a taxable German shareholder than to a tax-exempt or foreign shareholder. This results in a penalty for foreign investors who buy and hold German dividend-paying stocks. I document that, as a result of the credit, the ex-day drop exceeds the dividend by more than one-half of the tax credit, and show that futures and option prices embed more than one-half of the tax credit. The existence of the credit creates opportunities for cross-border tax arbitrage—in which foreign holders of German stock transfer the dividend to German shareholders—and implies that it is tax efficient for foreign investors to hold derivatives rather than investing directly in German stocks. The empirical findings are consistent with costly tax arbitrage activity by German investors, who face tax risk due to antiarbitrage rules. Since dividend tax credits exist in many other countries, the findings are potentially of broad interest.